An ionic liquid–organics–water ternary biphasic system enhances the 5-hydroxymethylfurfural yield in catalytic conversion of glucose at high concentrations. Issue 8 (3rd August 2015) - Zhou, Jinxia; Xia, Zhi; Huang, Tingyu; Yan, Peifang; Xu, Wenjuan; Xu, Zhanwei; Wang, Jianji; Zhang, Z. Conrad
<x xml:space="preserve">Abstract</x> An ionic liquid–organics–water ternary biphasic system has high 5-HMF productivity and separation efficiency in the CrCl3 catalyzed conversion of glucose at high concentrations.